Septic Pulmonary Embolism: A Case Series, Proposed Set of Diagnostic Criteria, and Review of the Literature. Issue 1 (January 2019) - Chengsupanimit, Tayoot; Sundaram, Baskaran; Kane, Gregory C.
Abstract : Septic pulmonary embolism is an unusual manifestation of bloodstream infection that presents with fever, chest pain, fatigue, and radiographic evidence of pulmonary infarction. We report on 4 cases of septic pulmonary embolism and provide a comprehensive review of this important entity. We also propose a modified set of diagnostic criteria in order to evaluate suspected cases clinically and confirm this diagnosis.